1973
DOI: 10.1111/j.1442-9071.1973.tb00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Macular-Foveal Capillaries in Human Retina

Abstract: Summary The occurrence of atypical vascularization of the macular‐foveal zone in 20 eyes of 17 patients is described. The significance of this fluorescein stereoangiographic finding is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Cases with no or only an extremely small capillary-free zone in the macula have been reported [8,9] and these abnormalities are reported to be found frequently in prema ture infants [10,11]. On this basis, it has been hypothesized that during fetal development the vascular network is present in the mac ular area which then disappears forming the capillary-free zone either before or after birth [10].…”
mentioning
confidence: 99%
“…Cases with no or only an extremely small capillary-free zone in the macula have been reported [8,9] and these abnormalities are reported to be found frequently in prema ture infants [10,11]. On this basis, it has been hypothesized that during fetal development the vascular network is present in the mac ular area which then disappears forming the capillary-free zone either before or after birth [10].…”
mentioning
confidence: 99%
“…Bird and Weale [10] initially demonstrated that blood vessels were common in the center of the fo vea. Yeung and colleagues [15] presented 17 healthy subjects with FAZ replaced by a poly gonal net of normal-looking capillaries or transected by capillaries. In the present study, 5 (18.5%) out of 27 control subjects had the FAZ covered or transected by a capillary net work.…”
Section: Discussionmentioning
confidence: 99%
“…Lowenstein (1942) and Yeoung (1973) demonstrated a capillary-free area which measured 0 165 to 0 07 mm respectively. The variability in size does not appear to prejudice foveal function (Yeoung, 1973).…”
Section: Commentmentioning
confidence: 98%
“…Lowenstein (1942) and Yeoung (1973) demonstrated a capillary-free area which measured 0 165 to 0 07 mm respectively. The variability in size does not appear to prejudice foveal function (Yeoung, 1973). Bird and Weale (1974) showed that capillaries can cross the central foveal area in patients with normal visual acuity, and similar findings were obtained by Shikano and Shimizu (1968).…”
Section: Commentmentioning
confidence: 98%
See 1 more Smart Citation